Recurrent subaortic membrane causing subvalvular aortic stenosis 13 years after primary surgical resection - Takx, Richard A. P.; Schoepf, U. Joseph; Friedman, Brad; Hlavacek, Anthony M.; Henzler, Thomas (Journal of cardiovascular computed tomography, 2011)
This case demonstrates the use of cardiac CT angiography as part of the preoperative evaluation of a recurrent subaortic memebrane in a 23-year-old women. A subaortic membrane is a rare finding on coronary CT angiography and typically consists of a thin fibrous membrane in the left ventricular outflow tract (LVOT). The resulting turbulent flow may lead to LVOT obstruction and aortic insufficiency.